DNA damage tolerance in hematopoietic stem and progenitor cells in mice - Pilzecker, Bas; Buoninfante, Olimpia Alessandra; van den Berk, Paul; Lancini, Cesare; Song, Ji-Ying; Citterio, Elisabetta; Jacobs, Heinz (Proceedings of the National Academy of Sciences - PNAS, 2017)
DNA damage tolerance (DDT) enables bypassing of DNA lesions during replication, thereby preventing fork stalling, replication stress, and secondary DNA damage related to fork stalling. Three modes of DDT have been documented: translesion synthesis (TLS), template switching (TS), and repriming. TLS and TS depend on site-specific PCNA K164 monoubiquitination and polyubiquitination, respectively. To investigate the role of DDT in maintaining hematopoietic stem cells (HSCs) and progenitors, we used mice as a unique DDT-defective mouse model. Analysis of the composition of HSCs and HSC-derived multipotent progenitors (MPPs) revealed a significantly reduced number of HSCs, likely owing to increased differentiation of HSCs toward myeloid/erythroid-associated MPP2s. This skewing came at the expense of the number of lymphoid-primed MPP4s, which appeared to be compensated for by increased MPP4 proliferation. Furthermore, defective DDT decreased the numbers of MPP-derived common lymphoid progenitor (CLP), common myeloid progenitor (CMP), megakaryocyte-erythroid progenitor (MEP), and granulocyte-macrophage progenitor (GMP) cells, accompanied by increased cell cycle arrest in CMPs. The HSC and MPP phenotypes are reminiscent of premature aging and stressed hematopoiesis, and indeed progressed with age and were exacerbated on cisplatin exposure. Bone marrow transplantations revealed a strong cell intrinsic defect of DDT-deficient HSCs in reconstituting lethally irradiated mice and a strong competitive disadvantage when cotransplanted with wild-type HSCs. These findings indicate a critical role of DDT in maintaining HSCs and progenitor cells, and in preventing premature aging.